Special Supplement of abstracts presented during the 7th MUHAS Scientific Conference in 2019 (Tanzania Medical Journal, 2019)
Tanzania Medical Journal is proud to be collaborating with the Organizing committee of the MUHAS Scientific Conference in publishing the conference abstracts accepted for oral presentation at the 7th MUHAS Scientific Conference that was held on 27th -28th June 2019, Dar es salaam Tanzania. This conference had a theme: “Health Research and Innovation for Economic Sustainable Development”. The abstracts are listed in clusters as they were presented during the conference, and whenever appropriated first authors affiliation is also listed. The scientific committee for this conference was responsible for peer review of the abstracts.